Reducing Poverty in Estonia Through Activation and Better Targeting - Flèche, Sarah (OECD Economics Department Working Papers, 2012)
The crisis revealed the need for a strategic review of the existing social protection system in Estonia. Extreme income fluctuations on one side and low social benefits on the other side exposed fragile groups in the population to a significant poverty risk. The government has recently commissioned several studies to prepare a systematic reform of the system. The spectrum of options is wide and includes increased generosity, further efficiency gains, strengthening incentives, better access to services and more ambitious activation. In particular, all support programmes should be designed to maximise the prospects of re-integrating beneficiaries into employment. Social benefit recipients should therefore become regular clients of the unemployment insurance offices, and they should benefit from job search assistance and active labour market policies. Scarce resources should be more targeted to those in greatest need. Addressing the large inflows into the disability system is a priority